EGFR-TKIs or EGFR-TKIs combination treatments for untreated advanced EGFR-mutated NSCLC: a network meta-analysis - Ao Liu; Xiaoming Wang; Lian Wang; Han Zhuang; Liubo Xiong; Xiao Gan; Qian Wang; Guanyu Tao (BMC Cancer)
Abstract Background Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) and EGFR-TKI combination treatments have become the standard first-line treatments for EGFR-mutated non-small cell lung cancer (NSCLC) patients. However, the best option has yet to be determined. This study compares the efficacy and safety of various first-line EGFR-TKI monotherapies and combination treatments for advanced EGFR-mutated NSCLC. Methods We searched PubMed, Embase, the Cochrane Central Register of Controlled Clinical Trials databases, and several international conferences to identify randomized controlled trials reporting on first-line EGFR-TKI treatments for patients with advanced EGFR-mutated NSCLC. The study quality was assessed using the revised tool for risk of bias in randomized trials. The efficacy and safety outcomes of the included treatments were compared by network meta-analysis based on a frequentist approach. Results We identified 26 trials (8,359 patients) investigating 14 treatment groups, including first, second, and third-generation EGFR-TKIs and their combination treatments. Osimertinib plus chemotherapy and lazertinib plus amivantamab showed the highest efficacy in improving progression-free survival. New third-generation EGFR-TKIs demonstrated comparable efficacy to osimertinib alone but did not surpass it. Subgroup analyses revealed slight variation in treatment efficacy based on mutation types and patient demographics. Combination treatments were associated with a higher incidence of adverse events. Conclusion These results reveal that osimertinib plus chemotherapy and lazertinib plus amivantamab are superior first-line options for patients with advanced EGFR-mutated NSCLC. However, these combinations are associated with higher adverse event rates.